The best practice of marketing strategies for the Malaysian business event industry from experts' perspective - Mohd Nasir, Hazira; Alagas, Elangkovan Narayanan; Amin, Muslim; Zamzuri, Norol Hamiza; Mohd Zairul, Mohd (Emerald Publishing, 2021)
Purpose: This paper aims to explore the best practices in marketing strategies for the Malaysian business event industry. Design/methodology/approach: A qualitative methodology was adopted to collect primary data from semi-structured interviews. The informants included ten experts from the Malaysian business event industry. The data collected were then grouped using the ATLAS.ti (v.8) software for thematic analysis. A trustworthiness assessment was applied to increase the credibility and ensure the rigour of the qualitative findings. Findings: The qualitative results revealed the following final themes: event marketing, the marketing plan, the 7 Ps of the marketing mix, strength, weaknesses, opportunities and threats (SWOT) analysis and traditional and digital marketing. Interestingly, three inductive themes were also emerged as follows: relationship marketing, unique selling points (USPs) and key opinion leaders. Research limitations/implications: This study looked at Malaysian business events and focused only on findings from the industry expert's perspective. In the future, further investigation may concentrate on other business event industry players such as destination marketing companies, airline operators, travel intermediaries, clients, suppliers, universities and the government. Practical implications: The findings offer a holistic approach to increase Malaysia's competitiveness among other primary business event host destinations in the Asian-Pacific, improve its worldwide and Asian-Pacific rankings and better position the country as a preferred business event destination during the coronavirus disease 2019 (COVID-19) pandemic. Originality/value: This is the first such study to date, which has never been explored in qualitative academic research. This study has substantial implications for various business event industry stakeholders in Malaysia.